Evaluation of hematological profiles in pediatrics: a focus on blood cell indices and electrolyte changes in febrile seizures - Kannan, Kowsalya; Gurumurthy, Haripriya; Maraicar, Nabila Safreen Vappu; Mohan, Mathesh (International Journal of Contemporary Pediatrics, 2025)
Background: Febrile seizures (FS) are the most common neurological disorder in children, often associated with systemic and hematological changes. Laboratory investigations play a crucial role in identifying potential biomarkers that may aid in risk evaluation and management. This study aims to evaluate various laboratory parameters, including platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), Hemoglobin (Hgb), serum sodium, platelet count (PLT), and white blood cell count (WBC), to assess their role as predictive markers in febrile seizures. Methods: A prospective observational study was conducted on pediatric patients diagnosed with febrile seizures. Blood samples were analyzed for hematological and biochemical markers. The collected data were statistically analyzed to determine significant associations between these parameters and febrile seizures. Results: The study findings highlight variations in hematological and biochemical markers among febrile seizure patients. Altered PLR and NLR levels were observed, indicating a possible inflammatory response. MCV, MCH, and Hgb levels were assessed for potential anemia-related influences, while serum sodium levels were evaluated for their role in seizure pathophysiology. Conclusion: The study provides insights into the laboratory profile of febrile seizure patients, which may help in early identification, risk assessment, and management. Further large-scale studies are required to validate these findings and establish potential predictive markers.